CORELLATION BETWEEN NUTRITIONAL STATUS AND HEAD CIRCUMFERENCE IN CHIRLDREN WITH SPECIAL NEEDS WITH SPEECH DELAY - Septi Adelia; Rini Andriani; Wilson Wilson (Universitas Muhammadiyah Ponorogo, 2022)
Growth and development of a child is influenced by several factors, including nutritional status and head circumference. Childreen who experience growth and developmental disorders are called children with special needs who have several categories, one of them is interference in speech and language. This study aims to determine the relationship between nutritional status and head circumference in children with special needs in Psychiatric Hospital Sungai Bangkong Pontianak. This study is an analytic survey with a cross sectional design on 40 children with special needs in Psychiatric Hospital Sungai Bangkong Pontianak. The results of the study were tested with the Somers'd test, chi-square test, and Fisher's test with the help of the computer program. The results of the bivariate analysis showed that there was no significant relationship between nutritional status and speech delay (p: 0,376). Bivariate analysis showed that there was no significant relationship between head circumference and speech delay (p: 0,537).